Perinatal outcomes in twin pregnancies complicated by maternal morbidity: evidence from the WHO Multicountry Survey on Maternal and Newborn Health - Danielly S. Santana; Carla Silveira; Maria L. Costa; Renato T. Souza; Fernanda G. Surita; João P. Souza; Syeda Batool Mazhar; Kapila Jayaratne; Zahida Qureshi; Maria H. Sousa; Joshua P. Vogel; José G. Cecatti; et al. (BMC, 2018)
Abstract Background Twin pregnancy was associated with significantly higher rates of adverse neonatal and perinatal outcomes, especially for the second twin. In addition, the maternal complications (potentially life-threatening conditions-PLTC, maternal near miss-MNM, and maternal mortality-MM) are directly related to twin pregnancy and independently associated with adverse perinatal outcome. The objective of the preset study is to evaluate perinatal outcomes associated with twin pregnancies, stratified by severe maternal morbidity and order of birth. Methods Secondary analysis of the WHO Multicountry Survey on Maternal and Newborn Health (WHOMCS), a cross-sectional study implemented in 29 countries. Data from 8568 twin deliveries were compared with 308,127 singleton deliveries. The occurrence of adverse perinatal outcomes and maternal complications were assessed. Factors independently associated with adverse perinatal outcomes were reported with adjusted PR (Prevalence Ratio) and 95%CI. Results The occurrence of severe maternal morbidity and maternal death was significantly higher among twin compared to singleton pregnancies in all regions. Twin deliveries were associated with higher rates of preterm delivery (37.1%), Apgar scores less than 7 at 5th minute (7.8 and 10.1% respectively for first and second twins), low birth weight (53.2% for the first and 61.1% for the second twin), stillbirth (3.6% for the first and 5.7% for the second twin), early neonatal death (3.5% for the first and 5.2% for the second twin), admission to NICU (23.6% for the first and 29.3% for the second twin) and any adverse perinatal outcomes (67% for the first twin and 72.3% for the second). Outcomes were consistently worse for the second twin across all outcomes. Poisson multiple regression analysis identified several factors independently associated with an adverse perinatal outcome, including both maternal complications and twin pregnancy. Conclusion Twin pregnancy is significantly associated with severe maternal morbidity and with worse perinatal outcomes, especially for the second twin.